2000
DOI: 10.1086/301587
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of the X-Ray-selected EMSS Sample of BL Lacertae Objects

Abstract: We present updated and complete radio, optical and X-ray data for BL Lacs in the Einstein Medium Sensitivity Survey (EMSS). The complete "M91" sample first presented in Morris et al. is updated to include 26 BL Lacs in total and we define a new, virtually complete sample consisting of 41 EMSS BL Lacs (the "D40" sample). New high signal-to-noise, arcsecond-resolution VLA observations are also presented for eleven EMSS BL Lacs, completing VLA observations of the M91 sample. The addition of four new objects, as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
165
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(192 citation statements)
references
References 61 publications
25
165
2
Order By: Relevance
“…While our spectroscospic classification as a BL Lac object agrees with previous results, the redshift proposed here (z=0.89) is significantly different from that proposed by Rector et al (2000) (z=0.602). These latter authors did not find any evidence of emission line(s) in their spectrum, and based their tentative redshift determination on low SNR absorption features.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…While our spectroscospic classification as a BL Lac object agrees with previous results, the redshift proposed here (z=0.89) is significantly different from that proposed by Rector et al (2000) (z=0.602). These latter authors did not find any evidence of emission line(s) in their spectrum, and based their tentative redshift determination on low SNR absorption features.…”
Section: Resultssupporting
confidence: 73%
“…Moreover at the proposed redshift (z=0.89) we were able to reproduce quite well also the shape of the underlying optical continuum (see Figure 2). Finally we note that this source is strongly variable: at least a factor of 5.5 in the X-ray domain (by comparing the measured 0.1-2.4 keV flux with the flux in the ROSAT All Sky Survey) and a factor of 3 in the optical domain (by comparing our magnitude with the V mag =20 reported in Rector et al 2000), so this variability could explain the clear different shape from the optical spectra reported in Rector et al (2000) and that reported here (see Figure 2). At z=0.89 the observed X-ray spectrum is well described by a featureless power-law model (Γ = 2.21 +0.07 −0.06 ) with intrinsic N H = 1.9 × 10 21 cm −2 ; the intrinsic 2-10 keV luminosity is ∼ 3.7 × 10 45 erg s −1 .…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Notice that for the first time we can study the evolution of HBLs and LBLs within the same sample. Previous comparisons had been typically made between the 1 Jy (radio selected) and the EMSS samples (X-ray selected), although Rector et al (2000) did study the dependency of hV e /V a i on X-ray-to-radio flux ratios for the EMSS sample. Admittedly, the errors on the hV e /V a i values are rather large but this is the best that can be done at present.…”
Section: Evolutionmentioning
confidence: 99%
“…For this elusive class of objects the adopted selection criteria can affect the redshift distributions of the BL Lac objects and cause different cosmological evolution scenarios (see, e.g., the discussions in Bade et al 1998 andGiommi et al 2012). Radioselected BL Lac objects seem to display a positive evolution (i.e., either the number density or the luminosity shows a decrease with cosmic time), while a negative evolution or no evolution at all was proposed for X-ray-selected objects (Rector et al 2000;Rector & Stocke 2001;Caccianiga et al 2002;Beckmann et al 2003;Padovani et al 2007;Ajello et al 2009;Giommi et al 2009Giommi et al , 2012, and references therein). A continuum trend from slightly positive-evolution low-peaked BL Lac objects to strong negative-evolution high-peaked BL Lac objects was proposed (Rector et al 2000), and was thought to be related to the X-ray to radio flux ratio (Giommi et al 1999(Giommi et al , 2012.…”
Section: Introductionmentioning
confidence: 99%